SIMULASI EFEK TURBO CYCLONE TERHADAP KARAKTERISTIK ALIRAN UDARA PADA SALURAN UDARA SUATU MOTOR BAKAR MENGGUNAKAN COMPUTATIONAL FLUID DYNAMICS - Utomo, Tony Suryo (ROTASI, 2006)
Turbo Cyclone is an additional device for an internal combustion engine, which can be used to create swirledflows of air in the intake channel. Swirling flow has abilities to improve fuel/air mixing efficiency, increasingcombustion intensity and stabilizing the combustion flame and also raising the flame propagation speed thus theeffective combustion can be achieved. Turbo Cyclone installation will affect its airflow characteristics, e.g. turbulenceintensity and pressure drop. The blade design has a great effect to the magnitude of turbulence intensity and pressuredrop. The CFD simulation shows that turbo cyclone installation does have effect to the turbulence intensity andpressure drop. Further analysis with blade design variation gives the results that the wider blade angle the bigger itsturbulence intensity and so does the pressure drop. Turbo Cyclone without holes on its blades also has morecontribution in raising those two parameters than Turbo Cyclone with holes on its blades. In this case model 7 has thelargest turbulence intensity and pressure drop at all air inlet velocity, that is 105,32 Pa and 1,52 at air inlet 6,099 m/s,570,45 Pa and 3,62 at air inlet 14,52 m/s, and also 937,73 Pa and 4,64 at air inlet 18,634 m/s.